FUZZY APPROACH FOR THE ESTIMATION OF THE AMOUNT OF PURIFIED PROTEIN IMMUNOGLOBULIN G FROM THE PROTEIN A AFFINITY COLUMN - ABDUL MANNAN; PON.SRIGAYATRI (International Journal of Pharma and Bio Sciences, 2013)
In the process of protein purification, the amount of proteins isolated with the help of commercial protein purification processes remains uncertain and vague. The present paper proposed a set of fuzzy rule system based on Fuzzy Expert System (FES) which predicts the amount of purified proteins based upon the flow rate of the protein in column, pH and binding capacity of resin to desired protein present in column. The potential benefit of this fuzzy system is to develop a computational model which helps the scientific community to determine the amount of purified protein before starting the process of purification and saving time and related procedural works.